The Role of Business Process Modeling Notation in Process Improvement: A Critical Review - Adieb Mursyada (RSF Press, 2024)
Business Process Modeling Notation (BPMN) has emerged as a crucial element in augmenting organizational efficiency and driving process enhancement across diverse industries.Based on this condition, this study, through acritical review wants to examinethe impact of BPMNon organizational process improvement, highlighting its role in enhancing operational efficiency, reducing errors, and facilitating better communication among stakeholders. Through a comprehensive analysis of literature across various industries, this review substantiates the hypothesis that BPMN significantly contributes to process improvement initiatives. This study explores BPMN’s adaptability, integration with other tools, and effectiveness in real-world applications. In addition, the review identifies gaps in current research and suggests BPMN’s potential in digital transformation efforts. This synthesis confirms the essential role of BPMN in achieving operational excellence and underscores the need for further exploration of its capabilities.